Gains of regional cooperation: Environmental problems and solutions - Anil Markandya (University of Bonn, Center for Development Research (ZEF), 2004)
Cooperation between the states of the Caucasus and Central Asia is paramount in solving the region's environmental problems. Given the acute socio-economic difficulties they face, their slow progress is understandable. Serious environmental and socio-economic consequences cumulate as the neglect persists. Increased oil and gas revenues (for those who have access to these resources) cannot ease such consequences. The exploitation of oil revenues may benefit the national economy, but it does not generally provide enough for the poor local communities that depend on the natural resources of the Caspian for their livelihoods. The international community must therefore help to promote cooperation within the region. The Caspian Environment Program provides an example of the kinds of things that need to be done, but more resources are needed for sustainable development. Perhaps the oil companies will do more, given their long-term stake in the region. In addition, the countries themselves can, and should, allocate more funds for the sustainable development of the region, but co-ordinated programs will be required to dissuade governments from seeking a free ride on the good actions of the others.
Keywords: 320; Environmental Economics and Policy; Internationale Umweltpolitik; Region; Nachhaltige Entwicklung; Kaspisches Meer; Kaukasus; Zentralasien